Transarterial Chemoembolization With or Without Systemic Therapy for Unresectable Hepatocellular Carcinoma: A Retrospective Comparative Study - Chengxiang Guo; Weiran Du; Yiwen Chen; Wenbo Xiao; Ke Sun; Yan Shen; Min Zhang; Jian Wu; Shunliang Gao; Jun Yu; Risheng Que; Xing Xue; et al. (Cancer Medicine, 2025)
ABSTRACT Introduction Standard treatments provide limited benefits for patients with intermediate‐ or advanced‐stage hepatocellular carcinoma (HCC). This retrospective observational study aimed to assess the potential improvements in outcomes associated with systemic therapies in patients receiving transarterial chemoembolization (TACE) for initially unresectable HCC. Methods Between February 2019 and March 2023, we reviewed patients diagnosed with intermediate‐to‐advanced HCC who were treated with either TACE or TACE combined with antiangiogenic agents and immune checkpoint inhibitors (combination therapy) as their initial treatment. To address potential confounding biases, patients were further stratified into surgical and non‐surgical cohorts, and separate analyses were conducted. The primary endpoints were progression‐free survival (PFS) and overall survival (OS), with safety profiles also evaluated. Results Among 279 patients with initially unresectable intermediate or advanced HCC, 156 successfully underwent curative‐intent liver resection after preoperative treatments (TACE group, n = 69; combination group, n = 87), while 123 patients continued with non‐surgical treatments (TACE group, n = 31; combination group, n = 92). After propensity score matching, 26 matched patient pairs were generated within the non‐surgical cohort. The combination group exhibited significantly improved PFS in non‐surgical patients compared with the TACE group (9.4 vs. 7.2 months, p = 0.043). Cox proportional hazards analysis further confirmed that combination therapy was associated with improved PFS (hazard ratio = 0.476, 95% confidence interval: 0.257–0.883, p = 0.019). For surgical patients exceeding the up‐to‐seven criteria, the combination group demonstrated superior median PFS (18.0 vs. 14.6 months, p = 0.03) and OS (not reached vs. 50.1 months, p = 0.049) compared with the TACE group. Adverse events were manageable, with no treatment‐related fatalities reported. Conclusion Combination therapy with TACE demonstrated enhanced survival benefits for patients with intermediate to advanced HCC, particularly in surgical patients with higher tumor burdens.